Etiopathenogenic bases for the development of pulmonary hypertension and chronic heart failure in patients with ischemic heart disease in combination with arterial hypertension (literature review, observation of the authors) - Matsegora, N. A.; Мitasova, N. Yu. (Journal of Education, Health and Sport, 2017)
Research aim. To study epidemiological and general clinical features of patients with IHD in combination with AH, complicated with chronic heart failure (СHF 2А and 2B). Results of the research. Based on a review of the literature and the results of the authors' study, it is shown that CHF in patients with IHD in combination with AH is accompanied by pulmonary hypertension already at early stages of clinical development of CHF. We examined 120 patients with IHD in combination with AH at the age of 44 to 90 years (mean age 72.29 ± 1.66), the majority was men (86.7%), and this is because the studies were carried out in the cardiology departmentMilitaryMedicalClinicalCenterof the Southern Region. Among the patients with CHF 2A studied, middle-aged people accounted for 20.4%, and for advanced and senile patients - 79.6%. More severe heart failure (CH 2B) was diagnosed mainly in declining and elderly patients (95.4%), which indicated a more severe character of the course of IHD and AH in this contingent. The leading risk factors for the formation of CH 2A and CH 2B in patients with IHD in combination with AH were: acute myocardial infarction (65.4%), chronic myocardial ischemia (angina pectoris) (34.6%), violations of carbohydrate and lipid metabolism (2 / 3 cases), the rate of hypodynamia (66%) and stressful events (35.8%). Data of subjective research showed that a leading clinical syndrome was a shortness of breath at small (CHF 2А) and insignificant (СНF 2B) physical activity, and also in a night-time, that accompanied by an unproductive cough. From data of review of literature, it is explained by the haemodynamic overload of small circle with the increase of pressure in a pulmonary artery and reflects the degree of heart failure. The edematous syndrome in the form of foot pathes to the level of the shins was registered in patients from CH 2A in 66.7%, and in CHF 2B - in 77.3% of cases, and in the latter had a significant density. In the study of blood pressure in patients with coronary artery disease in combination with AH, depending on the severity of heart failure, it was found that patients with CHF 2A AP were elevated, and in patients with CHF 2B (p 0.05) - normal or low, which coincides with the data of literature and is explained by a decrease in the fraction of the ejection of the left ventricle as a result of the development of heart failure against the background of pulmonary hypertension.